Parental/caregiver racial-ethnic socialization during early childhood: a meta-ethnographic review - Quick, Kaitlin N.; Mendez Smith, Julia; Coard, Stephanie Irby; Jensen, Michaeline (Frontiers in Psychology, 2026)
IntroductionRacial-ethnic socialization (RES) is an ongoing developmental process through which parents and caregivers share information, values, and perspectives about race and ethnicity with their children. While there is a substantial body of research on RES during adolescence, little empirical work has focused on early childhood.MethodsThis review applied a systematic search strategy and meta-ethnographic methods to examine and integrate the existing qualitative research on RES during early childhood. Out of 1,900 screened studies, 277 were reviewed for eligibility, and 27 met the inclusion criteria.ResultsFindings from the seven phase meta-ethnographic review process highlight the dynamic and multifaceted nature of RES in parenting. Parents' own life experiences strongly shape their values, beliefs, and intentions for RES, which in turn inform the approaches and messages they use with their children. These strategies are often interrelated but can also be influenced by competing beliefs triggered by children's characteristics, experiences, and environments.DiscussionOverall, the synthesis supports prior claims that RES in early childhood is deeply embedded within general parenting practices and family dynamics. It also identifies critical gaps in the literature (e.g., limited diversity of study samples in terms of family structures and racial-ethnic backgrounds) that future research should address.